Methods of multivariate analysis - Rencher, Alvin C., 1934-; Christensen, William F., 1970- (New Jersey : Wiley, 2012)
"This new edition, now with a co-author, offers a complete and up-to-date examination of the field. The authors have streamlined previously tedious topics, such as multivariate regression and MANOVA techniques, to add newer, more timely content. Each chapter contains exercises, providing readers with the opportunity to test and extend their understanding. The new edition also presents several expanded topics in Kronecker product; prediction errors; maximum likelihood estimation; and selective key, but accessible proofs. This resource meets the needs of both statistics majors and those of students and professionals in other fields"--
Includes bibliographical references and index.
Keywords: Multivariate analysis